Stress eating: an online survey of eating behaviours, comfort foods, and healthy food substitutes in German adults - Kathrin Gemesi; Sophie Laura Holzmann; Birgit Kaiser; Monika Wintergerst; Martin Lurz; Georg Groh; Markus Böhm; Helmut Krcmar; Kurt Gedrich; Hans Hauner; Christina Holzapfel (BMC, 2022)
Abstract Background In many people, stress is associated with changes in eating behaviour. Food products consumed during stress (comfort foods) are often unhealthy. It is rather unknown what comfort foods are consumed in Germany and what healthier food products are considered as alternatives to support stress-eaters in making healthier food choices. Methods This online survey was conducted in spring 2021 throughout Germany. Participants were digitally recruited by newsletters, homepages, social media, and mailing lists. The survey included a standardized questionnaire with items concerning e.g. sociodemography, stress, and nutrition. Comfort foods were pre-selected through literature search and food substitutes were defined and discussed by experts. Analyses examined comfort food consumption and substitute preferences dependent on sex, age, body mass index (BMI), and being a self-identified stress-eater. The statistical analysis was performed using R. Results Survey participants were mostly female (80.6%, 994/1234), had a mean age of 31.4 ± 12.8 years and a mean BMI of 23.4 ± 4.3 kg/m2. Participants stated, that the two favourite comfort foods were chocolate (consumed often/very often by 48.3%, 596/1234) and coffee (consumed often/very often by 45.9%, 566/1234). Regarding food substitutes, the most frequently named alternative food for chocolate and cookies was fresh fruits (for chocolate: 74.4%, 815/1096, for cookies: 62.6%, 565/902). Tea without added sugar (64.4%, 541/840) was the preferred substitute for coffee. Almost 50% of participants (48.1%, 594/1234) identified themselves as stress-eaters, of which 68.9% (408/592) stated to eat (very) often more than usual in subjective stress situations. Conclusions The results from this work suggest that specific comfort foods and substitutes are preferred by the participants in stressful situations. This knowledge about food choices and substitutes should be investigated in further studies to improve eating behaviour in stressful situations. Trial registration The survey was registered in the German Register of Clinical Studies (Registration number: DRKS00023984 ).